Technology Acceptance Model to Implementation of Electronic Medical Record (EMR’s) at Clinic of Rumah Sehat Keluarga Jember - Atma Deharja; Meiranda Normarisa Azis; Novita Nuraini; Angga Rahagiyanto; Maya Weka Santi; Muhammad Yunus (Universitas Aisyah Pringsewu, 2022)
The Rumah Sehat Keluarga Clinic is one of the clinics in Jember that has just implemented electronic medical records (RME) at the end of October 2020. Based on observations made on January 4, 2021, at the Rumah Sehat Keluarga Clinic, it is known that there are several obstacles in implementing the electronic medical record system. outpatient treatment indicating that analysis is necessary. This study aims to analyze the application of outpatient electronic medical records at the Rumah Sehat Keluarga Clinic. Identification of problems using the TAM (Technology Acceptance Model) method by reviewing aspects of external variables, aspects of perceived usefulness, aspects of perceived ease of use, and aspects of behavioral intention to use. This type of research is qualitative with data collection methods, namely interviews, observation, documentation and brainstorming. The subjects of this study are the head of the clinic and the medical record officer. The results showed that based on aspects of external variables, several constraining factors were obtained including the absence of guidelines for using RME for new or old users and there was a diagnosis menu that had not been integrated with the ICD 10 database. Aspects of perceived usefulness, namely the use of electronic medical records in the clinic made the work of the officers faster and more efficient. The perceived ease of use aspect showed that receiving electronic medical records is considered easy to understand, flexible enough with the work of officers and easy to use to help work. Based on the aspect of behavioral intention to use, even though there are several obstacles in its application, outpatients show interest in RME and they will use it in the future. Abstrak: Klinik Rumah Sehat Keluarga baru menerapkan Rekam Medis Elektronik (RME) pada akhir Oktober 2020. Berdasarkan pengamatan terdapat kendala dalam penerapannya yang menunjukkan perlu dilakukan analisis. Tujuan penelitian ini untuk menganalisis penerapan rekam medis elektronik rawat jalan Klinik Rumah Sehat Keluarga. Identifikasi permasalahan menggunakan metode TAM (Technology Acceptance Model) dengan meninjau dari aspek variable luar (external variable), aspek kebermanfaatan (perceived usefulness), aspek kemudahan (perceived ease of use), dan aspek minat (behavioral intention to use). Jenis penelitian ini kualitatif dengan metode pengumpulan data yaitu wawancara, observasi, dokumentasi dan brainstorming. Subjek penelitian ini adalah kepala klinik dan petugas rekam medis. Hasil penelitian menunjukkan bahwa berdasarkan aspek variabel luar (external variable) diperoleh faktor kendala diantaranya tidak adanya panduan penggunaan RME bagi pengguna baru atau lama dan terdapat menu diagnosis yang belum terintegrasi dengan database ICD 10. Aspek kebermanfaatan (perceived usefulness) yaitu penggunaan rekam medis elektronik di klinik membuat pekerjaan petugas menjadi lebih cepat dan efisien. Aspek kemudahan (perceived ease of use) menunjukkan dalam penerimaan rekam medis elektronik dinilai mudah dipahami, cukup fleksibel dengan pekerjaan petugas serta mudah digunakan untuk membantu pekerjaan. Berdasarkan aspek minat (behavioral intention to use) yaitu petugas rawat jalan menunjukkan minatnya terhadap RME serta berencana menggunakannya di masa yang akan datang.